Una revisión de la literatura sobre crowdsourcing - Gregorio T. López Maciel; Ana Pertusa Palacios; Erika L. Gonzalez Rosas (Journal of Innovation & Knowledge (JIK), 2017)
This paper offers a review of the theory published on crowdsourcing tools from de point of view of the concept's adoption by researchers. Crowdsourcing is a concept that includes many of the online collaboration activities performed by crowds in response to an open call. The paper offers a perspective on the incremental amount of publications already available as an indicator of the level of such adoption, given that the adoption process in general takes time because there has to be a critical mass of ideas conformed by experts. This paper includes a review on the theoretical concepts related to crowdsourcing and technological adoption. Systematic search has been done and the obtained information is included. Finally some conclusions are delivered.
Keywords: O32; O33; 650; Crowdsourcing; Social media; Technological adoption; Open innovation